Multiple System Atrophy: Many Lessons from the Transcriptome. (June 2018) - Curry-Hyde, Ashton; Chen, Bei Jun; Ueberham, Uwe; Arendt, Thomas; Janitz, Michael
Multiple system atrophy (MSA) is a complex, multifactorial, debilitating neurodegenerative disease that is often misdiagnosed and misunderstood. MSA has two subclasses, MSA-P and MSA-C, defined by the dominance of parkinsonism or cerebellar dysfunction in the earlier stages of disease, coupled with dysautonomia. This distinction between subclasses becomes largely redundant as the disease progresses. Aggregation of α-synuclein is a clinical marker used to confirm MSA diagnoses, which can only be performed postmortem. Transcriptome profiling provides in-depth information about the diseased state and can contribute to further understanding of MSA, enabling easier and more rapid diagnosis as well as contributing to improving the quality of life of people with MSA. Currently, there is no method of diagnosing MSA with certainty, and there is no cure for this disease. This review provides an update on current advances in investigations of molecular pathology of MSA with particular focus on perturbation of individual gene expression and MSA transcriptome.